2016
DOI: 10.1007/s00128-016-1930-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Biological Effects of Endocrine Disrupting Chemicals in the Yellow River (Zhengzhou Section)

Abstract: Estrogenic activities of river water from four representative cross-sections of the Yellow River (Zhengzhou section) and their effects on reproduction and development of fish were assessed. MVLN assay showed estradiol equivalents of river water from Yiluohe, Xinmanghe, Qinhe and Huayuankou cross-sections were 1.09 ± 0.11, 0.72 ± 0.01, 1.19 ± 0.19 and 0.80 ± 0.04 ng/L, respectively. Significant vitellogenin (VTG) inductions were observed in adult male Japanese madaka (Oryzias latipes) after 30 days of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To analyze the estrogenic activity correlation between the main stream and the tributaries, further material analysis was required. Compared with the estrogenic activity in the lower Yellow River Basin reported by other studies, the activity in this study was relatively high; the highest estrogen activity was 0.21 ng L −1 in the lower reaches of Tongguan of the Yellow River in rainy season [36]; while the estrogen activity in Zhengzhou basin of the Yellow River was 0.72~1.19 ng L −1 [37]. However, it should be noted that the sampling sites reported above were located in the main stream of the Yellow River and not in rural areas, and there have been few reports on environmental surface water in the rural basin of the Yellow River.…”
Section: Estrogenic Toxicity Assessment By Yescontrasting
confidence: 90%
“…To analyze the estrogenic activity correlation between the main stream and the tributaries, further material analysis was required. Compared with the estrogenic activity in the lower Yellow River Basin reported by other studies, the activity in this study was relatively high; the highest estrogen activity was 0.21 ng L −1 in the lower reaches of Tongguan of the Yellow River in rainy season [36]; while the estrogen activity in Zhengzhou basin of the Yellow River was 0.72~1.19 ng L −1 [37]. However, it should be noted that the sampling sites reported above were located in the main stream of the Yellow River and not in rural areas, and there have been few reports on environmental surface water in the rural basin of the Yellow River.…”
Section: Estrogenic Toxicity Assessment By Yescontrasting
confidence: 90%
“…For example, Chen et al assessed the human health risks of some POPs, such as organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ether (PBDEs), and found that PCBs and OCPs in the trunk water of the Yellow River and in soil and maize irrigated with river water pose potential carcinogenic and non-carcinogenic risks [ 33 ]. Song et al determined the content of endocrine-disrupting chemicals (ECDs) in the Yellow River, and found that ECDs existed in the river (Zhengzhou section) and could pose reproductive risks and developmental impairment to fish in the Yiluohe and Qinhe cross-sections [ 34 ]. Feng et al determined the content of antibiotics in the Yellow River, and detected high concentrations of norfloxacin, carbamazepine, and 5,5-diphenylhydantoin [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strict related locals with the presence of species under threat of extinction deserve special attention with relation to the dumping of contaminants that may complicate the reproduction of them and, consequently, contribute to their extinction. Song and Wang (2016) performed a study to investigate the estrogenic activities of four regions from Yellow River, by assays developed with the MVLN cell line. Besides establishing the EEQs of the samples, the VTG induction, GSI, and the hepatosomatic index (HSI) in adult males of the rice fishes (Oryzias latipes) exposed to the water collect from the river were verified.…”
Section: Aquatic Environmentmentioning
confidence: 99%